Daniel Buren : Halifax : 7 days - 6 placements - 7 colors from a work done by Daniel Buren = 7 jours - 6 emplacements - 7 couleurs d'après un travail de Daniel Buren. (Halifax, 1974)
Announcement of a series of works done by Daniel Buren in Halifax April 1973, reprinted for a summary of a sequence of 7 post cards, souvenirs of these works (Peter Sheppard photographer)
Location : Corner of Granville st. and Buckingham St., Halifax, Nova Scotia, Canada
Engels
Frans
boek
Keywords: Buren, Daniel